Chronic Discrimination and Sleep Problems in Late Life: Religious Involvement as Buffer. (December 2018) - Bierman, Alex; Lee, Yeonjung; Schieman, Scott
The association between chronic discrimination and sleep problems is important to examine in older adults because sleep is highly reactive to stress and impaired sleep has diverse adverse health effects. The association between chronic discrimination and sleep problems may, however, be confounded by a number of time-stable influences, and this association may also vary by religious involvement. In three waves (2006, 2010, and 2014) of the Health and Retirement Study ( N = 7, 130), the overall association between chronic discrimination and sleep problems is negated in econometric models that control for all time-stable sources of confounding. Religious involvement does not modify this association for men, but a significant association is found among women who do not attend religious services. These analyses suggest that the association between chronic discrimination and sleep quality in late life is substantially inflated due to unobserved time-stable confounders, although women who do not attend religious services may be at risk.